Geomorphology and environmental history in the Drava valley, near Berzence - Viczián, István; Zatykó, Csilla (Hungarian Geographical Bulletin, 2011)
This geomorphological and environmental history case study aims at reconstructing the environmental conditions and the different ways of land use in the surroundings of Berzence in the Drava valley. The area’s geomorphological evolution is examined with regards to the natural processes and the human impact that formed the landscape. The results indicate a tendency in the surface waters and underground waters for drying, mainly due to water regulation and canalization works. Findings from archaeological field walks, certified documents, and old maps are integrated in the reconstruction. Special attention is given to medieval fishing areas, iron processing sites and settlement structures.